Cumulative exposure of TDF is associated with kidney tubulopathy whether it is currently used or discontinued. (14th January 2018) - Nishijima, Takeshi; Mutoh, Yoshikazu; Kawasaki, Yohei; Tomonari, Kiyomi; Kikuchi, Yoshimi; Gatanaga, Hiroyuki; Oka, Shinichi
Abstract : Objective: Tenofovir disoproxil fumarate (TDF) increases the risk of kidney tubular dysfunction (KTD). This study was conducted to elucidate whether KTD persists after discontinuation of TDF. Design: A prospective cross-sectional study which enrolled 941 HIV-1-infected patients. Methods: KTD was predefined as the presence of at least two abnormalities among the five tubular markers (fractional excretion of phosphate, fractional excretion of uric acid, β2 microglobulinuria, N-acetyl-β-D-glucosaminidase, nondiabetic glycosuria). Logistic regression model was used to examine the association between KTD and cumulative TDF use, as well as current status of TDF use. Results: In total, 94% of study patients were men (median age 45, estimated glomerular filtration rate 75 ml/min per 1.73 m 2, CD4 + 575 cells/μl. About 98% were on antiretroviral therapy. In total, 64% of the patients ever used TDF and 39% currently used TDF. Twenty-nine percent used TDF for more than 5 years. KTD was diagnosed in 116 (12%) patients. In multivariate model, more than 5 years of TDF exposure and current TDF use [odds ratio (OR) 4.2, 95% confidence interval (CI) 2.37–7.56], more than 5 years and past TDF use (OR 2.4, 95% CI 1.09–5.33), less than 5 years and current TDF (OR 2.4, 95% CI 1.24–4.85), and less than 5 years and past TDF (OR 2.4, 95% CI 1.22–4.64) were all significantly associated with KTD, with never TDF use as reference. The results were the same using 4 and 3 years of exposure as the cutoff. However, with 2 years exposure, both less than 2 years and current TDF (OR 2.3, 95% CI 0.84–6.20) and less than 2 years and past TDF (OR 1.9, 95% CI 0.73–4.93) were not associated with KTD, whereas both more than 2 years and current TDF and more than 2 years and past TDF were associated. Conclusion: The association between cumulative TDF use and KTD was strong and robust. The results of the study suggested that TDF-related KTD might persist after discontinuation of TDF if patients used TDF for more than 2 years. Abstract : Supplemental Digital Content is available in the text